Assessing The Resilience Of Drainage Infrastructure Under Extreme Rainfall Events - Lauzuary (CV. SINAR HOWUHOWU, 2025)
Extreme rainfall events have become more frequent and intense due to climate change, posing serious challenges to urban drainage infrastructure. This study assesses the resilience of drainage systems under extreme rainfall through hydrological modeling, field surveys, and resilience index analysis. Results indicate that many existing drainage networks were designed using outdated rainfall assumptions, leading to recurrent flooding and capacity failures. Structural measures alone were found insufficient to withstand extreme rainfall; instead, integrated approaches combining engineering improvements and real-time monitoring are required. Land-use change and urbanization further exacerbate drainage inefficiencies by reducing natural infiltration. The study highlights that proactive maintenance, adaptive design, and hybrid green–gray infrastructure can significantly enhance resilience. Recommendations include incorporating dynamic rainfall models, deploying smart monitoring technologies, and adopting policy frameworks that embed resilience assessments in urban planning. This integrated approach is crucial for ensuring sustainable, adaptive drainage systems in the face of evolving climatic conditions.